Authority without power : - Haley, John Owen (Oxford University Press, 1991)
This book offers a comprehensive interpretive study of the role of law in contemporary Japan. Haley argues that the weakness of legal controls throughout Japanese history has assured the development and strength of informal community controls based on custom and consensus to maintain order--an order characterized by remarkable stability, with an equally significant degree of autonomy for individuals, communities, and businesses. Haley concludes by showing how Japan's weak legal system has reinforced preexisting patterns of extralegal social control, thus explaining many of the fundamental paradoxes of political and social life in contemporary Japan.